Implementasi Algoritma Caesar Ciper untuk Mengidentifikasi Keaslian Sepatu Kulit Parm.id dengan Menggunakan QR Code - Tito Sugiharto; Yati Nurhayati; Mochamad Abdul Gofur (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2020)
Now day the development of information technology and security are very rapid and important for human life, it cannot be denied that this digital era requires humans to be effective and efficient in gaining information. The security and the authenticity of a product are very important aspects of human life, including the security of authenticity in the field of copyright, for that in a shoe industry, especially leather shoes in Indonesia, there are a lot of misuses of fake leather shoes, so that these factors can affect the quality of leather shoes and it has an impact on the decreasing income obtained by genuine leather shoe craftsmen in Indonesia. This study aims to facilitate customers to be able to distinguish the authenticity of genuine Parm.id leather shoes and it can guarantee more trust to customers. To overcome this problem, in the process of securing the authenticity of leather shoes, parm.id uses the Caesar Ciper algorithm by generating it into a QR Code. The research method uses a Rational Unified Process (RUP) by implementing the Caesar Ciper algorithm which is a cryptographic algorithm by shifting letters of the alphabet. application that is built using an android smartphone, with PHP programming languages, JAVA and MySQL as database storage. In the process of using this application, the customers will scan the QR Code data in the shoe, when it has been scanned and the data is valid, the application will display data on parm.id shoes with compositions in the shoes that customers scan, but when the QR data The shoe code that customers scan is invalid, it can be ascertained that the shoe is not produced by parm.id and it can be said that the shoe is not original. The result of this study is in the form of application that is able to provide convenience and guarantee more trust to parm.id shoes customers.keywords: Android, Caesar Ciper algorithm, encryption, description, rational unified process (RUP)